Hydrodynamics, Water Quality and GIS Applications in River Systems: A Global and Indian Perspective - Verma, Sunita; Tripathi, Chandra Kishore (Indian Forester, 2025)
This study examines the interplay between hydrodynamics, water quality, and the use of GIS in river systems, with a focus on global applications and Indian case studies. By integrating hydrodynamic modeling, sediment transport analysis, and GIS-based tools, the research highlights methodologies for effective river basin management. Key findings include the role of GIS in flood prediction, sediment tracking, and water quality monitoring, offeringin sights for sustainable river management.